Numerical Analysis of the Informational Parameters of the Magnetic Fields in the Area of the Defects of Wheel Pairs Axes - Shvedchykova, Iryna; Mohmed Jasim Jasim, Jasim; Shevchenko, Olexandr; Soloshych, Iryna (International Journal of Engineering and Technology, 2018)
The article is devoted to the problem in diagnostic for axes of wheel sets of rolling stock at the railroad lines. It shows that the time counter method of magnetic powder control has low productivity and is characterized by high subjectivity and the impossibility of automating the control process. To eliminate these defects and improve the reliability for detection of defects on the surface of the stepped axis a method based on the using of fluxgate transducer is proposed. It was carried out the analysis of magnetic fields near the surface of the axles of wheel sets using the developed mathematical models, which made it possible to calculate both the defect fields and the stray field of the stepped surface of axis. Spatial and frequency selection of useful signals based on the analysis of information parameters of magnetic fields of stray of surface and subsurface defects and fields induced by the stepped surface of the magnetized axis is proved.Â Â